2015
DOI: 10.2105/ajph.2014.302437
|View full text |Cite
|
Sign up to set email alerts
|

When Advocacy Obscures Accuracy Online: Digital Pandemics of Public Health Misinformation Through an Antifluoride Case Study

Abstract: Network sociology may be as influential as the information content and scientific validity of a particular health topic discussed using social media. Public health must employ social strategies for improved communication management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 27 publications
0
46
0
4
Order By: Relevance
“…Similar patterns are observed in discussions on water fluoridation, as memorably invoked in the 1964 movie Dr. Strangelove. Seymour et al (2015) analysed the anti-fluoride network online and found that strong ties among the community are obstacles for expert opinions to be accepted. This indicates that social homogeneity may well be the primary driver of content diffusion and clustering.…”
Section: Othersmentioning
confidence: 99%
“…Similar patterns are observed in discussions on water fluoridation, as memorably invoked in the 1964 movie Dr. Strangelove. Seymour et al (2015) analysed the anti-fluoride network online and found that strong ties among the community are obstacles for expert opinions to be accepted. This indicates that social homogeneity may well be the primary driver of content diffusion and clustering.…”
Section: Othersmentioning
confidence: 99%
“…A study of digital pandemics of public health misinformation found that in online discussions about a sample scientific publication, half of social media users encountered negative and nonempirical content unrelated to the original paper. 3 The authors refer to this problem as "social diffusion," and concluded that public health organizations must employ new social media strategies to improve their communication of public health information.At the clinical level, doctors attempting to change the minds of patients who cling to potentially harmful health myths and misconceptions will need patience. People are unlikely to abandon long-held beliefs overnight, especially if it means abandoning online communities that have become an important part of their lives.…”
mentioning
confidence: 99%
“…These comments put little credence in scientific research evidence, and instead appealed to anecdotes. The study of the spread of misinformation has been described as network sociology, and "it may be as influential as the information content and scientific validity of a particular health topic discussed using social media" ( [32], p. 517). It may be useful for future research to examine how an appeal to anecdotes affects the spread of public health messages.…”
Section: Discussionmentioning
confidence: 99%